Hollow cathode discharge in low pressure oxygen: transient mode - Bazhenov, V.Yu.; Matsevich, S.V.; Piun, V.M.; Tsiolko, V.V. (Вопросы атомной науки и техники, 2015)
Glow characteristics of the discharge with cylindrical hollow cathode at oxygen pressure in a range of 0.015…0.09 Torr are determined. Dependencies of radial electric field in the plasma on the discharge parameters are defined, and particular fact of creation at pressure higher than ~ 0.06 Torr the potential barrier at the boundary between negative glow plasma and cathode layer, which limits ion escaping to the cathode. As well, limits of the discharge glow characteristics are determined, which result in appearance of the hollow cathode effect. Встановлено характеристики горіння розряду з циліндричним порожнистим катодом при тисках кисню 0,015…0,09 Торр. Знайдено залежності радіального електричного поля в плазмі від параметрів розряду, зокрема, встановлено факт утворення при тисках більше ~ 0,06 Торр потенціального бар’єру на границі між плазмою негативного світіння та катодним шаром, який обмежує вихід іонів на катод. Також встановлено граничні характеристики горіння розряду, при яких починає проявлятися ефект порожнистого катодa. Установлены характеристики горения разряда с цилиндрическим полым катодом при давлениях кислорода 0,015…0,09 Торр. Найдены зависимости радиального электрического поля в плазме от параметров разряда, в частности, установлен факт образования при давлениях больше ~ 0,06 Торр потенциального барьера на границе между плазмой отрицательного свечения и катодным слоем, ограничивающего уход ионов на катод. Также установлены граничные ха-рактеристики горения разряда, при которых начинает проявляться эффект полого катода.